May all your fences have gates : essays on the drama of August Wilson - Nadel, Alan, 1947- (UPCC book collections on Project MUSE., 1994)
This stimulating collection of essays, the first comprehensive critical examination of the work of two-time Pulitzer Prize-winning playwright August Wilson, deals individually with his five major plays and also addresses issues crucial to Wilson's canon: the role of history, the relationship of African ritual to African American drama, gender relations in the African American community, music and cultural identity, the influence of Romare Bearden's collages, and the politics of drama. The collection includes essays by virtually all the scholars who have currently published on Wilson a.